AFRICA’S DEVELOPMENT, ENVIRONMENT AND ALDO LEOPOLD’S LAND ETHIC - Ikeke, M. O. (UDS International Journal of Development, 2019)
It is a recognizable fact that Africa, like other continents, needs development in this contemporary time. Africa is considered to be one of the least, if not the least developed continent in the world in terms of modern infrastructure and information communication technology. It is also a recognized fact that every form of development has environmental impacts. The enormous environmental cost of development is often neglected in Africa. Both African countries and companies have devoted less than expected to environmental conservation. Africa needs both development and environmental conservation. To navigate the tension between development and the environment, a new worldview that prioritizes environmental conservation and at the same time promotes authentic development is imperative. Aspects of Aldo Leopold’s Land Ethic can be useful in this regard. Analytically these issues are investigated in this paper which finds and concludes that Africa needs development while at the same time conserving her environment. Keywords: Africa, development, environment, land ethic, and Aldo Leopold